Scientific Uncertainty and Biodiversity Inventory - Subedi, Indra Prasad (Nepal Journal of Science and Technology, 2021)
All sciences, including biological science, have uncertainty, and they complicate theoretical questions. Uncertainty essentially is a mark of good science, and its efficacious communication is even essential for better decisions. Explaining the research work uncertainties indicates that the scientists are aware of the vital difference between the known and the unknown. Uncertainty is equally significant in biodiversity studies. Species composition of any area can’t be predicted with certainty because of interwoven relationships between species diversity and climatic and anthropogenic factors. Good survey planning with acceptable animal welfare practices could lead to asymptote for inventory of any particular area. Scientists can handle uncertainty in their studies by sensible statistics and reasonably large sample size.